Hearing the voice of the Shingo principles : creating sustainable cultures of enterprise excellence - Miller, Robert Derald (Routledge, 2018)
For more than 50 years, organizations of all types have struggled to achieve lasting benefits from the many tools and programs associated with various continuous-improvement initiatives. In fact, the notion of "continuous" improvement is largely a misnomer -- for many organizations, continuous improvement has been anything but continuous. Responding to this challenge, Hearing the Voice of the Shingo Principles chronicles key insights that went into development of the Shingo Model for Operational Excellence at Utah State University.This book helps leaders understand their role in building sustainable cultures of enterprise excellence - That is, how to keep the entire enterprise focused on guiding principles that will change beliefs, behaviors, and the overall mindset. In addition, managers will learn how to align systems with principles so that they drive ideal, principle-based behaviors - the goal is for every leader to realign their values with the voice of principles and become an example so that every associate becomes self-motivated to continuously improve every aspect for which they are accountable.To build long-term credibility of the Shingo Prize, the author and his team had to understand what was causing such wide variation in results and make certain they were only recognizing those organizations that could demonstrate sustainability of improvements over the long term. They found that sustainability depended less on application of the tools for improvement than on embedding principles deep into the culture of the organization from top to bottom and side to side.